Analisis Faktor Penyebab Keterlambatan Pengembalian Berkas Rekam Medis Rawat Jalan di RSUD Besuki - Nashrul Kholiqir Rohman; Rossalina Adi Wijayanti; Novita Nuraini; Riskha Dora Candra Dewi (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
The return of medical record files is an activity to return the completed medicalrecord file to the medical record unit after the patient returns home. The delay inreturning the outpatient medical record file at the Besuki Hospital in the thirdquarter of 2021 reached 63.87%. This study aims to analyze the factors that causedelays in returning outpatient medical record files at Besuki Hospital. This type ofresearch is qualitative. Data collection techniques using interviews, observation,documentation and ultrasound. The results of this study are individual factors thatcause delays in returning outpatient medical record files, namely officers do notunderstand the SOP for returning outpatient medical record files and officershave not been able to complete medical record files because the doctor's workshift is only briefly at Besuki Hospital. Psychological factors that cause delays inreturning outpatient medical record files are the lack of awareness andresponsibility of officers towards returning medical record files and medicalrecord distribution officers have never been motivated by the head of the medicalrecord. The organizational factor causing the delay in returning outpatientmedical records is that there is no compensation given by the hospital to theofficer and the head of the medical record has not been so firm in handling casesof late return of outpatient medical record files. Besuki Regional GeneralHospital is expected to provide rewards or rewards to officers; make SOPs forreturning outpatient medical record files and socialize them to officers; sanctionsare given to officers who are late in returning outpatient medical record files; thehead of the medical record is even more assertive to his subordinates andprovides motivation.